(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study was conducted in the Animal field of Animal Production Department-College of Agriculture- Al-Qasim Green University to investigate the effect of utilization of two levels of dietary crude protein (CP), 12.5 and 14.5% with or without addition of BioSB-Gold probiotic (P) into concentrate diet at rate of 1 kg/ton on rumen fermentation characteristics in Awassi lambs. Sixteen male Awassi lambs with average weight of 18.76 ± 3.34 and age of 4-6 months were used. Lambs were randomly allocated into individual pens at rate of 4 lambs per each treatments. Concentrate diets were offered at 2.5% of live body weight with two meals, at morning and evening. Wheat straw was offered ad libitum. Samples of rumen liquid were withdrawn from all animals before feeding and 3 and 6 hours later. Results revealed that increasing CP levels from 12.5 th 14.5% did not affect pH values significantly but it resulted in a significant increase (P<0.01) in concentrations of ammonia nitrogen (NH3-N) and total volatile fatty acids (TVFA) from 6.31 to 6.78 mg/100 ml and from 12.53 to 13.35 mmol/100 ml respectively. Addition of probiotic increased pH (P<0.01) from 6.86 to 7.03. Significant (P<0.01) increase in concentrations of NH3-N from 5.94 to 7.15 mg/100 ml and in concentrations of TVFA too from 12.47 to 13.41 mmol/100 ml was also seen due to addition of P.